Does ferritin level affect the outcomes of autologous stem cell transplantation equally in all diseases? - Uysal, Ayse; Erkurt, Mehmet Ali; Kuku, Irfan; Kaya, Emin; Sarici, Ahmet; Berber, Ilhami; Cirik, Salih (Pergamon-Elsevier Science Ltd, 2023)
Background: In this retrospective study, we evaluated the effect of ferritin levels on the outcomes of autologous stem cell transplantation in patients with MM or lymphoma.Methods: In this study, 170 patients with measured ferritin levels within one month before transplantation who underwent ASCT with the diagnosis of MM or lymphoma were evaluated. The cut-off value of ferritin was determined as 500 ng/mL to evaluate the transplant outcomes in both groups. The hematological recovery status/duration, febrile neutropenia rate, hospitalization time, transplant-related mortality (TRM) in the first 100 days, and OS were evaluated according to the ferritin levelResults: Of all patients, 105 (61,8%) were diagnosed with MM and 65 (38.2%) with lymphoma. Ferritin levels had no statistically significant effect on the engraftment status/times, the febrile neutropenia rates, and hospitalization times of both lymphoma and myeloma patients (p > .05). Ferritin level was not significantly associated with TRM in MM (p = .224). However, in lymphoma, ferritin level was significantly associated with TRM (33.3% for ferritin level & GE;500 ng/L vs. 5.3% for ferritin level ng/mL, p = .005). There was no statistically significant correlation between ferritin value and OS in MM group [ferritin level & GE; 500 ng/L: 39.9 months (95% CI: 33.7-46.1) and ferritin level 500 ng/mL: 39.4 months (95% CI: 36.5-42.2), p = .446]. Ferritin level was significantly associated with OS in patients with lymphoma [ferritin level & GE; 500 ng/L: 22.1 months 95% CI: 14.7-29.5), ferritin level 500 ng/mL: 27.3 months (95% CI: 22.4-32.2), p = .038]Conclusion: High ferritin level is important prognostic factor on survival after ASCT in patients with lymphoma.
Keywords: Autologous stem cell transplantation; Ferritin; Lymphoma; Multiple myeloma